MASLEMBING TEACHING MATERIALS CONTAINING ETHNOMATHEMATICS: INNOVATION IN PROBLEM-BASED MATHEMATICS LEARNING IN ELEMENTARY SCHOOLS - Istiqomah, Istiqomah; Bintoro, Henry Suryo; Ismaya, Erik Aditia (UNIVERSITAS MUHAMMADIYAH METRO, 2025)
This study aims to obtain a product in the form of MASLEMBING teaching materials containing ethnomathematics on the subject of probability for grade VI of elementary school. This research is a development research that uses the ADDIE design model with the stages of analysis, design, development, implementation, and evaluation. Data collection techniques use questionnaires, learning outcome tests, observation, and documentation. This research instrument is in the form of a questionnaire sheet, a learning outcome test sheet, which is then analyzed using qualitative and quantitative data. Qualitative data used are in the form of sentences, pictures, and charts. Quantitative data is collected by conducting validity tests, practicality tests, and effectiveness tests. The developed product is validated by material experts, media experts, and language experts. The results of the study show that the validation test score obtained an average score of 3.3, with a very good category. Based on the results of the student response questionnaire, a score of 3.30 was obtained, and the results of the teacher response obtained a score of 3.57, with a very good category. Based on the results of the effectiveness test, the results of the N-Gain test on the pretest and posttest scores in the experimental class obtained an average difference of 0.53 with moderate criteria, so the level of effectiveness is effective. The results of the Independent T Test comparison test showed that the significance value was 0.000 less than 0.05, so it can be concluded that there is a significant difference between the posttest results of the experimental class and the control class. With this, the MASLEMBING teaching materials containing ethnomathematics for grade VI elementary school students are effective, practical, and suitable for use in classroom learning.